Compression Study of Two Point Discrimination (2PD) Test between Normal and Blind People\'s Hand in Decade 10-20 - Akram Azad; Esmaeil Ebrahimi (University of Social Welfare and Rehabilitation Sciences, 2001)
Objective: Two point discrimination (2PD) test is a sensory functional test that is both available and valid. This test is used in hand injuries and neurological examination, whose perception takes place in the sensory cortical region. Materials & Methods: In this study 2PD test was evaluated in 240 normal and blind boys and girls in the range of 10-20 years in Tehran (Cross-sectional descriptive analysis). This test was evaluated on right and left hands by on instrument results. Results: The 2PD value of the normal subjects were greater than that of the blind subjects (specially at age 10-Th). The boys’ 2PD values were greater than girls. At age 20 years, the value of 2PD was greater than that of l0-th years. The 2PD value in dominant hands was greater than that of the undominant hands. Conclusion: The hierarchy of the accuracy of the results in the different regions of the hand is as follows: Thumb / Index / Little / Ring / Middle.